A porcine gluteus medius muscle genome-wide transcriptome analysis: dietary effects of omega-6 and omega-3 fatty acids on biological mechanisms. Issue 1 (December 2017) - Ogłuszka, Magdalena; Szostak, Agnieszka; te Pas, Marinus; Poławska, Ewa; Urbański, Paweł; Blicharski, Tadeusz; Pareek, Chandra; Juszczuk-Kubiak, Edyta; Dunkelberger, Jenelle; Horbańczuk, Jarosław; Pierzchała, Mariusz
Abstract Background The level of omega-6 and omega-3 polyunsaturated fatty acids can affect many cellular systems and function via nuclear receptors or the bioactive lipid regulation of gene expression. The objective of this study was to investigate changes in the muscle transcriptome and the biological functions regulated by increased consumption of omega-3 and omega-6 fatty acids in the pig gluteus medius muscle. Results The transcriptome of the gluteus medius muscle was studied for pigs subjected to either a control diet or a diet supplemented with linseed and rapeseed oil to increase polyunsaturated fatty acid content. Next-generation sequencing (NGS) was used to generate the muscle tissue transcriptome database pointing differentially expressed genes (DEG). Comparative expression analyses identified 749 genes significantly differing at least in the twofold of change between two groups of animals fed with divergent level of omega-3 and omega-6 fatty acids. The expression of 219 genes was upregulated, and the expression of 530 genes was downregulated in the group of pigs supplemented with omega-3 and omega-6 fatty acids in relation to control group pigs. Results of RNA-seq indicated a role of fatty acid in the regulation of the expression of genes which are essential for muscle tissue development and functioning. Functional analysis revealed that the identified genes were important for a number of biological processes including inflammatory response, signaling, lipid metabolism, and homeostasis. Conclusions Summarizing, obtained results provide strong evidence that omega-6 and omega-3 fatty acids regulate fundamental metabolic processes in muscle tissue development and functioning.